Ancient Egypt in the popular imagination : building a fantasy in film, literature, music and art - Huckvale, David, (McFarland & Co., 2012)
"Ancient Egypt has long been a source of fascination in Western popular culture. This work traces how films were inspired by writers like Bram Stoker and Sir Arthur Conan Doyle and by the art of Victorian painters. Similarly, it shows how the soundtracks to such films belong to a Romantic musical tradition stretching back beyond Verdi and Mozart"--Provided by publisher.